2021
DOI: 10.3390/nano11020416
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Surface Coverage of Aminophenyl Bonding Sites on Diazotised Glassy Carbon Electrodes for Optimised Electrochemical Biosensor Performance

Abstract: Electrochemical biosensors using carbon-based electrodes are being widely developed for the detection of a range of different diseases. Since their sensitivity depends on the surface coverage of bioreceptor moieties, it necessarily depends on the surface coverage of amine precursors. Electrochemical techniques, using ferrocene carboxylic acid as a rapid and cheap assay, were used to assess the surface coverage of amino-phenyl groups attached to the carbon electrode. While the number of electrons transferred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Tehrani et al, 2021, reported another immunosensor for detecting Aβ (1-42) using a diazotized GCE [74]. The surface of the GCE was electrochemically functionalized with an amino group (-NH 2 ) using cyclic voltammetry (CV) in a mixture solution of diazonium salt in an electrolyte of BU 4 NBF 4 and acetonitrile.…”
Section: Electrochemical Immunosensing Of Aβmentioning
confidence: 99%
“…Tehrani et al, 2021, reported another immunosensor for detecting Aβ (1-42) using a diazotized GCE [74]. The surface of the GCE was electrochemically functionalized with an amino group (-NH 2 ) using cyclic voltammetry (CV) in a mixture solution of diazonium salt in an electrolyte of BU 4 NBF 4 and acetonitrile.…”
Section: Electrochemical Immunosensing Of Aβmentioning
confidence: 99%
“…14 Typically, these assays utilize electrodeconfined p53 antigens. 15 However, on planar two-dimensional interfaces, the combined effects of moderately low epitope surface density (∼pmol/cm 2 ), 16 efficacy of large target (e.g., antibody) capture. Additionally, in protein-rich real samples (e.g., serum), recruitment against a large excess of background remains challenging.…”
mentioning
confidence: 99%
“… 14 Typically, these assays utilize electrode-confined p53 antigens. 15 However, on planar two-dimensional interfaces, the combined effects of moderately low epitope surface density (∼pmol/cm 2 ), 16 restricted target accessibility, and sluggish (planar) target diffusion serve to reduce the efficacy of large target (e.g., antibody) capture. Additionally, in protein-rich real samples (e.g.…”
mentioning
confidence: 99%